2020
DOI: 10.1182/bloodadvances.2020002650
|View full text |Cite
|
Sign up to set email alerts
|

Impaired natural killer cell counts and cytolytic activity in patients with severe COVID-19

Abstract: The global pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–driven coronavirus disease 2019 (COVID-19) has caused unprecedented human death and has seriously threatened the global economy. Early data suggest a surge in proinflammatory cytokines in patients with severe COVID-19, which has been associated with poor outcomes. We recently postulated that the inflammatory response in patients with severe COVID-19 disease is not inhibited by natural killer (NK) cells, resulting in a “cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 31 publications
10
99
0
2
Order By: Relevance
“…These questions remain unanswered. Stefania Varchetta et al 11 and Mohammed Osman et al 12 both observed a reduction of immature NK cells and a parallel enrichment in the mature subset. Of note, a significant reduction of IFN-γ secretion and degranulation activity, related to cytolytic activity, was observed in NK cells, which could be associated with exhaustion of NK cells.…”
Section: Innate Immune Responsesmentioning
confidence: 97%
See 1 more Smart Citation
“…These questions remain unanswered. Stefania Varchetta et al 11 and Mohammed Osman et al 12 both observed a reduction of immature NK cells and a parallel enrichment in the mature subset. Of note, a significant reduction of IFN-γ secretion and degranulation activity, related to cytolytic activity, was observed in NK cells, which could be associated with exhaustion of NK cells.…”
Section: Innate Immune Responsesmentioning
confidence: 97%
“…Among the studies on NK cells, many 11 , 12 , 13 , 14 focus on the significantly impaired NK cell counts but not the NK cell frequency observed in COVID-19 patients. They believe NK cells are hyperactivated in the acute phase of COVID-19, but return to the normal level after clinical recovery from COVID-19.…”
Section: Innate Immune Responsesmentioning
confidence: 99%
“…A previous study showed that migration of NK cells and macrophages helped clear SARS-CoV [ 176 ], and NK cells from COVID-19 patients showed increased perforin levels, providing a basis for understanding the role of NK cells in COVID-19 infections [ 177 ]. Given the importance of NK cells in acute viral infection, recent studies have demonstrated potential strategies for NK cell-based immunotherapy for COVID-19 [ 178 ]. An ongoing clinical trial in China investigates the use of NK cells for viral clearance in severe COVID-19-associated pneumonia patients (NCT04280224).…”
Section: Non-vaccination Treatment Options For Covid-19mentioning
confidence: 99%
“…Natural killer (NK) cells normally counteract these inflammatory signals by killing viral-infected cells, activated monocytes and T cells, thereby acting to reduce the inflammatory response [ 34 , 35 ]. In COVID-19, however, NK cell number and function are reduced in patients with severe disease, thereby potentiating the CRS [ 36 ].…”
Section: Immune Dysregulation In Covid-19 Aging and Rheumatic Diseasmentioning
confidence: 99%